PEMBELAJARAN MATERI KEBAHASAAN BERDASARKAN KURIKULUM 2006 DAN 2013 SERTA UPAYA PENINGKATAN KOMPETENSI GURU - Ghufron, Syamsul (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This research aimed at describing (1) the principle of language learning, (2) language materials in 2006 and 2013 curriculum, and (3) the efforts to increase teachers’ competence in the learning of language aspect. The data of this descriptive qualitative research were collected by means of documentation, recording and field note taking techniques. Language learning was done based on the principles that the learning of language component is the training on the understanding and the using of meaningful words, which is integrated into the learning of language skills, and this does not follow learning stages linguistically. Language materials in 2006 curriculum was shown from the following words: words choices, sentence, the correct language, literal, effective and polite. While in 2013 curriculum, the materials are more focused on identifying the text weaknesses, reviewing the text, evaluating the text and editing the text. Some efforts to improve teachers’ competence in learning language aspect have been done through language workshops, Teachers’ Team Work, Teachers of Subject Matter meeting, Professional organization on Language and language books, which are written based on students’ errors on language.